2021
DOI: 10.3389/fimmu.2021.767359
|View full text |Cite
|
Sign up to set email alerts
|

BpOmpW Antigen Stimulates the Necessary Protective T-Cell Responses Against Melioidosis

Abstract: Melioidosis is a potentially fatal bacterial disease caused by Burkholderia pseudomallei and is estimated to cause 89,000 deaths per year in endemic areas of Southeast Asia and Northern Australia. People with diabetes mellitus are most at risk of melioidosis, with a 12-fold increased susceptibility for severe disease. Interferon gamma (IFN-γ) responses from CD4 and CD8 T cells, but also from natural killer (NK) and natural killer T (NKT) cells, are necessary to eliminate the pathogen. We previously reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…A variety of defined proteins and polysaccharides, alone or as conjugates, that elicit varying degrees of protection have been previously assessed as potential vaccine components. These are exemplified by T3SS proteins (such as Bip), T6SS proteins (such as Hcp1), proteases, outer membrane proteins (OMPs, LolC), CPS, and LPS or purified OPS (Harland et al, 2007 ; Chin et al, 2012 ; Scott et al, 2014a , b , 2016 ; Gregory et al, 2015 ; Casey et al, 2016 ; Burtnick et al, 2018 ; Tomas-Cortazar et al, 2021 ). Hcp1 is required for assembly of the secretion apparatus and for the export of the T6SS virulence proteins (Mougous et al, 2006 ; Pukatzki et al, 2007 ; Brunet et al, 2014 ; Lim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of defined proteins and polysaccharides, alone or as conjugates, that elicit varying degrees of protection have been previously assessed as potential vaccine components. These are exemplified by T3SS proteins (such as Bip), T6SS proteins (such as Hcp1), proteases, outer membrane proteins (OMPs, LolC), CPS, and LPS or purified OPS (Harland et al, 2007 ; Chin et al, 2012 ; Scott et al, 2014a , b , 2016 ; Gregory et al, 2015 ; Casey et al, 2016 ; Burtnick et al, 2018 ; Tomas-Cortazar et al, 2021 ). Hcp1 is required for assembly of the secretion apparatus and for the export of the T6SS virulence proteins (Mougous et al, 2006 ; Pukatzki et al, 2007 ; Brunet et al, 2014 ; Lim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously developed a proteomic cell blot approach to identify bacterial proteins involved in epithelial cell attachment with a high potential to be effective vaccine antigens [ 34 ]. Using this approach, we have already identified an effective melioidosis vaccine candidate that protected mice for up to 81 days against Burkholderia pseudomallei, and that will be progressing to human studies in the near future [ 35 , 36 ]. Our aim was to extend this platform to identify novel protein adhesins specific to VTEC strains that may be effective vaccine antigens, either on their own or in combination with other antigens, to prevent human colonisation.…”
Section: Introductionmentioning
confidence: 99%
“…model in C57BL/6 mice demonstrated more promising results, with OmpW1 + SAS affording 75% protection on day 80 compared to 12.5% in the adjuvant alone group [ 174 ]. Splenocytes from vaccinated animals secreted significant levels of IFN-γ upon ex vivo stimulation with OmpW1, suggesting a strong Th1 response was mounted [ 175 ]. A notable downside of these experiments is that the study reported significant issues with protein solubility that could only be overcome by solubilizing the protein in urea.…”
Section: General Outer Membrane Proteins: β-Barrelsmentioning
confidence: 99%